"Going through the motions": A qualitative exploration of the impact of emergency medicine resident burnout on patient care. Issue 5 (27th September 2022) - Akhavan, Arvin Radfar; Strout, Tania D.; Germann, Carl A.; Nelson, Sara W.; Jauregui, Joshua; Lu, Dave W.
Abstract: Objectives: Burnout occurs frequently in emergency medicine (EM) residents and has been shown to have a negative impact on patient care. The specific effects of burnout on patient care are less well understood. This study qualitatively explores how burnout may change the way EM residents provide patient care. Methods: Qualitative data were obtained from a sample of 29 EM residents in four semistructured focus groups across four institutions in the United States in early 2019. Transcripts were coded and organized into major patient care themes. Results: Residents described many ways in which feelings of burnout negatively impacted patient care. These detrimental effects most often fit into one of four main themes: reduced motivation to care for patients, poor communication with patients, difficult interactions with health care colleagues, and impaired decision making. Conclusions: According to EM residents, burnout negatively impacts several important aspects of patient care. Resident engagement with clinical care, communication with patients and colleagues, and clinical care may suffer as a result of burnout.